Complete Mitochondrial Genome Sequence, Characteristics, and Phylogenetic Analysis of Oenanthe javanica - Xiaoyan Li; Qiuju Han; Mengyao Li; Qing Luo; Shunhua Zhu; Yangxia Zheng; Guofei Tan (Agronomy, 2023)
The plant mitochondria play a crucial role in various cellular energy synthesis and conversion processes and are essential for plant growth. Watercress (Oenanthe javanica) is a fast-growing vegetable with strong adaptability and wide cultivation range, and it possesses high nutritional value. In our study, we assembled the O. javanica mitochondrial genome using the Illumina and Nanopore sequencing platforms. The results revealed that the mitochondrial genome map of watercress has a circular structure of 384,074 bp, containing 28 tRNA genes, 3 rRNA genes, and 34 protein-coding genes. A total of 87 SSR (simple sequence repeat) loci were detected, with 99% composed of palindrome repeats and forward repeats, while no complementary repeats were identified. Codon preference analysis indicated that watercress prefers to use codons encoding leucine, isoleucine, and serine with a preference for A/U-ending codons. Phylogenetic analysis showed that watercress is closely related to species of Bupleurum, Apium, Angelica, and Daucus, with the closest evolutionary relationship observed with Saposhnikovia divaricata and Apium graveolens. This study provides a valuable resource for the study of the evolution and molecular breeding of watercress.